Tu infinita memoria: el largo camino de la militancia por la vida - Carla Peñaloza Palma (Les Cahiers ALHIM)
The crimes committed by dictatorships certainly meant the end of lives dedicated to militancy and popular struggle, but also for their families, the beginning of a path to achieve truth and justice. Not all relatives took this tour, however, there were those and especially women, that assumed this task as a new form of participation. We believe that women, who had their own militant experience, reconverted that partisan experience, to join the struggle of human rights organizations - in many cases create the organisations - and deploy their experience in pursuit of this cause for which no one was prepared and could not imagine that he would occupy much of the rest of their lives. From the disappearance of Doctor Enrique Paris -assessor of President Allende- from the Palacio de La Moneda, we will rebuild the road to search for his remains and that of justice, which culminated 45 years later with the conviction of those who were guilty of his death, detention and disappearance. The role played by María Eugenia, who was his wife, and who moves between party militancy and in human rights organizations, as a duality without complexes, and with the same objective. The defense of human rights and the end of the dictatorship. From his testimony, with the methodology and concepts of oral history - we will reconstruct the path that many women of his generation shared, in the search for truth and justice for an entire country.